KONSEP TRI UGERING NGAURIP MANGKUNEGARA IV SEBAGAI MOTIVASI PENGEMBANGAN KEWIRAUSAHAAN: PERSPEKTIF PENDIDIKAN ISLAM - Susiyanto, Susiyanto (Universitas Islam Sultan Agung, 2020)
ABSTRACTTri Ugering Ngaurip is a teaching developed by K.G.P.A.A. Mangkunegara IV, the king of the Kraton Mangkunegaran - Surakarta, in his work called Serat Wedhatama which contains three handles of life that must be owned by Javanese society. With these three concepts, the community will have a motivating guide in developing skills and achieving life direction based on Islamic perspectives that tend to be tassawuf.Tri ugering Ngaurip concept is interesting to be discussed because it reveals financial independence, guarding honor, and trying to gain intelligence. These three things are stated to be the handle of Javanese people's life which includes arta (wealth or economy), wirya (glory), and winasis (intelligence). In the realm of education development, it should be directed towards achieving these three categories. This concept is actually a description of the Javanese philosophical expression of